The Effect of Corporate Social Responsibility on firm payout policy: Role of shariah compliance in Pakistan - Akhtar, Yasmeen; Waris Malik, Bisma (UW Journal of Management Sciences, 2024)
Purpose: This study investigate the impact of CSR performance on firm dividend pay-outs. This study also investigates the direct and interacting role of firm Shariah compliance status on dividend pay-out. The majority of the research on the subject of how corporate social responsibility affects a firm's performance reports inconsistent and even contradictory findings. Moreover, many researchers exhibit that literature on Islamic finance is rare. Therefore, the current study contributes to the existing body of literature by presenting empirical shreds of evidence in emerging country as Pakistan Design and Methodology: Data for the current study has been collected from the official websites of the Pakistan Stock Exchange, companies’ specific websites, and open doors for the period of 2011 to 2021. The study used OLS, Fixed and Random affect model to investigate the link between the study variables. Findings: The findings reveal that CSR and SC both have a positive impact on dividend policies, with the interaction between them further enhancing this effect. Implications: The underlying study is useful for finance managers, policymakers, business analysts, and different academic researchers who find the impact of CSR and SC concerning the dividend pay-out of companies. Furthermore, it provides some remarkable suggestions for business stakeholders.